Самородна платина в породах Чемерпільської структури (Середнє Побужжя) - Павлюк, О.В.; Квасниця, В.М.; Кислюк, В.В.; Павлюк, В.М. (Мінералогічний журнал, 2010)
Починаючи з 1970-х рр. під час геологічних досліджень різними організаціями були виявлені аномалії платини на Північно-Тернуватській, Капітанській, Липовеньківській і Чемерпільській ділянках у Середньому Побужжі. Максимальний вміст платини (1 г/т) встановлений у Капітанському ультраосновному масиві. Однак самородна платина була зафіксована лише як мікроскопічні включення у різних мінералах. У 2009 р. самородна платина у вигляді окремих зерен вперше виявлена у Чемерпільській та Бакшинській структурах. Платиновмісні породи — розкислені, скарновані і березитизовані мафіти, кварцити, кальцифіри. Максимальний розмір зерен самородної платини сягає 0,75 мм. Всі зерна мають витягнуту пластинчасту форму. Хімічний склад платини, %: Pt (97,185—99,693), Pd (0—0,019), Os (0,012—0,099), Rh (0,213—0,309), Ni (0—0,009), Fe (0,009—0,023), Cu (0—0,008), Ag (0—0,007). Мінералогічні дослідження вказують на просторовий зв’язок платини з самородним золотом. C 1970-х гг. в процессе геологических исследований разными организациями были обнаружены аномалии платины на Северо-Терноватском, Капитанском, Липовеньковском и Чемерпольском участках в Среднем Побужье. Максимальное содержание (1 г/т) платины обнаружено в Капитанском ультраосновном массиве. Однако самородная платина была зафиксирована лишь в виде микроскопических включений в минералах-носителях. В 2009 г. самородная платина в виде отдельных зерен впервые обнаружена в Чемерпольской и Бакшинской структурах. Вмещающие породы — раскисленные, скарнированные, березитизированные мафиты, кварциты, кальцифиры. Максимальный размер зерен самородной платины достигает 0,75 мм. Все зерна имеют пластинчатую форму. Химический состав платины, %: Pt (97,185—99,693), Pd (0—0,019), Os (0,012—0,099), Rh (0,213—0,309), Ni (0—0,009), Fe (0,009—0,023), Cu (0—0,008), Ag (0—0,007). Минералогические исследования указывают на пространственную связь платины с самородным золотом. Holovanivs’ka sutural zone attracts people attention of researchers the prospect region for elements of platinum group exploration for a long time. Starting from the 1970’s in the course of geological survey platinum anoma lies were explored in the North-Ternuvats’ka, Kapitans’ka, Lypovenkivs’ka and Chemerpils’ka areas by different geological organizations. Maximal platinum content (1 g/t) was explored in the Kapitans’kyi ultrabasic massif. However native platinum was detected just as inclusions in minerals-bearers. In 2009 native platinum was explored for the first time in individual grains in the Chemerpil’ska and Bakshyns’ka structures. Chemerpil’ska structure is an association of eight oval synclinal formations from 120 to 700 metres in length and with steep to subvertical limbs dip which consist of the Archean metabasites and siliceous-carbonate igneous-sedimentary rocks. Most of their cores have high content of magnetite, often of industrial contents. Native platinum is set in amphibolite which is pierced by thin (to 1 cm) veins of quartz and of the fissures with aggregates of sulfides and clay minerals on its side. Steel-grey platinum grains with metallic lustre have elongated lamellar shape. Their sizes are (mm): 0.3×0.1; 0.5×0.1; 0.5×0.4; 0.7×0.1; 0.75×0.2. Gold content in the samples with platinum is 0.32 g/t. Satellite elements are zinc, argentum, satellite minerals are arsenopyrite, molybdenite, pyrrhotine. Chemical composition of the native platinum is the next, %: Pt (97.185—99.693), Pd (0—0.019), Os (0,012—0,099), Rh (0,213—0,309), Ni (0—0,009), Fe (0,009—0,023), Cu (0—0.008), Ag (0—0.007). Mineralogical researches point to the spatial connection between platinum and native gold. Materials for argumentation of genetic type of platinum mineralization of Chemerpil’ska structure are not sufficient to day. It is just possible to point out the connection of gold and platinum with deoxidated, scarning and greisening mafites. In the future it is necessary to continue geochemical and mineralogical researches of platinum mineralization of the Chemerpil’ska structure. It will promote a considerable growth of economic demand as the possible future deposit of noble metals.